Steam Reforming of Ethanol over Manganese and Iron Oxides for Hydrogen Production - Lidiya Yu. Dolgykh; Irina L. Stolyarchuk; Larisa A. Staraya; Inna V. Vasylenko; Yuri I. Pyatnitsky; Peter E. Strizhak (Adsorption Science & Technology)
MnO, Mn 2 O 3 , Fe 2 O 3 and Fe 3 O 4 are catalytically active for the steam reforming of ethanol. The main reaction products were acetaldehyde, acetone, CO 2 and H 2 in the temperature range of 300–550°C. At low temperatures, high selectivity for acetone (up to 75%) was observed for MnO. Based on the study results, the relation between product selectivity of the oxide catalysts and their acid–base/redox properties balance is suggested. The selectivity for hydrogen was about 80% for Fe 2 O 3 at 550°C with 100% ethanol conversion.